2021
DOI: 10.1021/acs.organomet.1c00503
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium and Palladium Complexes of N-Heterocyclic Olefin (NHO) Ligand Fused with the 9,10-Dihydro-9,10-ethanoanthracene Framework

Abstract: A saturated type of N-heterocyclic olefin (NHO) was synthesized by fusing 2-methyleneimidazolidine with a 9,10dihydro-9,10-ethanoanthracene framework, and rhodium and palladium complexes with this NHO were successfully obtained. The Tolman electronic parameter (TEP) value calculated using the Rh complex indicated that the electron-donating ability of the present saturated NHO was weaker than those of unsaturated NHOs. X-ray diffraction (XRD) studies of three Pd complexes confirmed that these complexes were [(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…30)) yet similar to that of the imidazole-based-NHO-Pd ( δ = −7.0 − (+0.99) ppm). 14 Increasing the substitution of C exo when going from 7aPd to 7bPd caused a downfield shift of about +11 ppm for the methyl group; in diastereomeric 7bPd , C exo resonated at δ = 10.7 and 10.9 ppm, which is close to the value expected in alkane series (+9 ppm). 45…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…30)) yet similar to that of the imidazole-based-NHO-Pd ( δ = −7.0 − (+0.99) ppm). 14 Increasing the substitution of C exo when going from 7aPd to 7bPd caused a downfield shift of about +11 ppm for the methyl group; in diastereomeric 7bPd , C exo resonated at δ = 10.7 and 10.9 ppm, which is close to the value expected in alkane series (+9 ppm). 45…”
Section: Resultsmentioning
confidence: 54%
“…1a) and have been identified as a promising new class of electron-rich and carbon-based ligands. [2][3][4][5][6][7][8][9][10] Imidazole-based NHO coordination compounds with Mo, 11 Rh, [12][13][14] Au, 10,13 W, 11,15 Ir, 5,16 Pd, 8,14 and Ti 17 have been reported. Their utility in catalysis is also documented.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that our original NHO ligand based on 2‐methyleneimidazolidine, which we refer to as DHASICH 2 , is useful in obtaining stable NHO−Pd complexes [22] . In that study, we decided to apply this motif to a core NHO for the development of a stable NHO−Pd catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that our original NHO ligand based on 2methyleneimidazolidine, which we refer to as DHASICH 2 , is useful in obtaining stable NHOÀ Pd complexes. [22] In that study, we decided to apply this motif to a core NHO for the development of a stable NHOÀ Pd catalyst. Our motif makes it relatively easy to introduce varied N-substituents, and this allows us to tune the steric environments around the olefin portions.…”
Section: Syntheses Of Nho Ligands and Their Pd Complexesmentioning
confidence: 99%
“…Indeed, since the discovery of the first transition metal‐NHO complex by Kaska and coworkers ( A ), [2] NHOs have been used as supporting ligands for transition metal‐mediated catalysis [3] . Examples of NHO‐transition metal complexes include those from the groups of Kuhn ( B ), [4] Ando and Ishizuka ( C ), [5] Rivard ( D ), [3d] and others (Chart 1) [6] . While multiple examples of transition metal complexes supported by neutral NHO donors can be found in the literature, examples of metal complexes bearing deprotonated, anionic N ‐heterocyclic olefins (aNHOs) remain rare [7] .…”
Section: Introductionmentioning
confidence: 99%